A revision of the genus Boesemania (Acanthuriformes: Sciaenidae), with clarification of the taxonomic status of Bahaba polykladiskos (Bleeker, 1852), and comments on its conservation - Lin, Bai-An; Seah, Ying Giat; Liu, Min; Hew, Simon; Janekitkarn, Sommai; Sirisuay, Soranuth; Vilasri, Veere; Vidthayanon, Chavalit; Grudpan, Chaiwut; Chang, Chih-Wei; Lin, Chien-Hsiang; Seymour, Mathew; et al. (Zootaxa, 2026)
The family Sciaenidae comprises around 300 species and 70 genera, with the Indo-West Pacific (IWP) region exhibiting the highest species richness. The genus Boesemania Trewavas, 1977 was established as a monotypic group based on the swim bladder and otolith morphology of Johnius microlepis Bleeker. Corvina polykladiskos Bleeker was recognized as the third species of the genus Bahaba. Based on recent morphology and molecular evidence, we assign Bahaba polykladiskos to the genus Boesemania. Boesemania polykladiskos is distinguished from Boesemania microlepis by its distinctly larger scales, the number of lateral-line, upper and lower trans-lateral-line rows, and sagitta and swim-bladder morphology. Phylogenetic analysis of 24 sciaenid species representing 23 genera from the Indo-West Pacific region further confirms that Boesemania is monophyletic and that Boesemania polykladiskos is the sister species of Boesemania microlepis. The two Boesemania species are commercially important fish in their native range and play an essential role in the global luxury dried swim-bladder trade. However, significant knowledge gaps persist regarding their ecology, biology, and population status. Consequently, this paper also addresses the need for further research and conservation measures for these species.